2022
DOI: 10.1212/wnl.0000000000200829
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Combination Antiretroviral Therapy on Cognition and Neuroimaging Biomarkers in Treatment-Naive People With HIV

Abstract: Background and Objectives:While combination antiretroviral therapy (cART) has dramatically increased the life expectancy of people with HIV (PWH), nearly 50% develop HIV-associated neurocognitive disorders (HAND)1. This may be due to previously uncontrolled HIV viral replication, immune activation maintained by residual viral replication2 or activation from other sources3, 4, or cART-associated neurotoxicity5. The aim of this study was to determine the effect of cART on cognition and neuroimaging biomarkers ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Results from neuropsychological assessment indicate that while HIV and CSVD were both individually associated with cognitive impairment, a combination of the two was most detrimental to cognition. While early initiation of cART is known to improve cognition to some extent (36), we have recently shown that over time, PLWH relapse into worsening cognition as compared to uninfected individuals (37). Our current findings suggest that the presence of CSVD in PLWH seems to confer a “double hit” on cognitive function and might not be the exclusive mechanism of NCI in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Results from neuropsychological assessment indicate that while HIV and CSVD were both individually associated with cognitive impairment, a combination of the two was most detrimental to cognition. While early initiation of cART is known to improve cognition to some extent (36), we have recently shown that over time, PLWH relapse into worsening cognition as compared to uninfected individuals (37). Our current findings suggest that the presence of CSVD in PLWH seems to confer a “double hit” on cognitive function and might not be the exclusive mechanism of NCI in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This study was reviewed and approved by the Research Subjects Review Board at the University of Rochester, and all study participants signed a written informed consent prior to undergoing study procedures. Details of the study cohort have been previously reported ( 45 ). For the analyses reported here, data on 88 unique study participants, 35 (32 male) treatment-naïve PWH and 53 (27 male) age-matched HIV− healthy controls were available at baseline.…”
Section: Methodsmentioning
confidence: 99%